Efficiency Evaluation of Airports Operations in Peru using Network Analysis - Mariño Uribe, Ricardo Jesús (2023)
The main characteristic of airport networks is their dynamism. The inclusion of a new air route or the insertion or closure of an airport alters the system and can even lead to the collapse of the network. It is for this reason that it is important to develop a Network Analysis, to know its typology, since its characteristics allow to determine the level of service that the system has and allow decision makers to propose strategies that allow them to achieve the efficiency of the system. However, in South America there is a gap in the analysis of airport networks; only Argentina and Brazil have managed to describe their networks and generate proposals for improvement. For this reason, this study has adopted the airport network of Peru, which has 66 authorized public airports and is in the process of increasing the capacity of its international airports and including new airport infrastructure. Within the framework of the multiple scenarios generated in this study, one third of the public airports do not have commercial flights, i.e., they are not part of the system. As a result, Peru has a poorly connected network with reduced cohesion and affiliation. In addition, the contribution of certain airports that connect those located in isolated cities and without other transportation options is observed. But above all, it shows the importance that the insertion of a new international airport achieves by significantly increasing the efficiency of the network. The conclusions of this study could have important implications for airport planning and could be considered in the preparation of the Civil Aviation Master Plans (CAMP) that the International Civil Aviation Organization (ICAO) urges its member states to develop in order to recognize the contributions of aviation to sustainable development, resulting in the stimulation of employment, trade, tourism and other areas of economic development.